Radiografía de los docentes en publicidad en España. Un estudio psicolaboral con enfoque de género - MARTÍN LLAGUNO, Marta; HERNÁNDEZ RUIZ, Alejandra (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2011)
Up until now, no studies had been conducted in Spain on the organization and work processes in the field of teaching and research in advertising, an area that, driven by technological, structural and educational advances, has experienced tremendous growth in recent decades. Recent studies have described work, organizational and attitudinal characteristics of advertising professionals. However, these issues have not been researched on the people who prepare these professionals: the faculty. This article advances a sociopsico labor analysis of the latter professionals. In a first study, we analyze the hierarchical organizational structure in the area of Audiovisual Communication and Advertising. This analysis uses the census of teachers from the MICINN (January 2009). The results show the masculinization of the category of associate professors, above the national average and show the existence of vertical segregation. In a second study, organizational and psico labor traits of teachers are valued based on a nationally representative sample of 174 Spanish teachers form 23 universities conducted from December 2008 to December 2009. With low levels of burnout and high levels of engagement, faculty perceive favourably the sector and their quality of life, but they like their work more than their universities.
Keywords: Attitudes; University context; Advertising; Gender studies; Faculty